Post-polio syndrome - somatosensory dysfunction and its relation to pain: a pilot study with quantitative sensory testing - Daniel Dahlgren; Kristian Borg; Eva Melin (Medical Journals Sweden, 2024)
Objective: To explore and characterize somatosensory dysfunction in patients with post-polio syndrome and chronic pain, by conducting examinations with Quantitative Sensory Testing. Design: A cross-sectional, descriptive, pilot study conducted during 1 month. Subjects/patients: Six patients with previously established post-polio syndrome and related chronic pain. Methods: All subjects underwent a neurological examination including neuromuscular function, bedside sensory testing, a thorough pain anamnesis, and pain drawing. Screening for neuropathic pain was done with 2 questionnaires. A comprehensive Quantitative Sensory Testing battery was conducted with z-score transformation of obtained data, enabling comparison with published reference values and the creation of sensory profiles, as well as comparison between the study site (more polio affected extremity) and internal control site (less affected extremity) for each patient. Results: Derived sensory profiles showed signs of increased prevalence of sensory aberrations compared with reference values, especially Mechanical Pain Thresholds, with significant deviation from reference data in 5 out of 6 patients. No obvious differences in sensory functions were seen between study sites and internal control sites. Conclusion: Post-polio syndrome may be correlated with a mechanical hyperalgesia/allodynia and might be correlated to a somatosensory dysfunction. With lack of evident side-to-side differences, the possibility of a generalized dysfunction in the somatosensory system might be considered.